P345 Another brick in the wall: Is hexane neuropathy a 'nodo-paranodopathy'?. Issue 9 (September 2017) - Baslo, Sezin Alpaydin; Ozturk, Oya; Dayan, Cengiz; Atakli, Dilek; Baslo, Mehmet Baris
Abstract : Objectives: To discuss electrophysiological follow-up of patients with n-hexane neuropathy and to remark overlaps with new concept nodo-paranodopathy. Methods: 3 males, aged between 18–39 years, working in shoe manufactory were evaluated. Occupational history, toxic substance exposures, neurologic examinations were noted and NCV-EMG were performed upon hospital admission and during clinical follow-up (1., 3., 4., 6. months; 1., 3., 9. months; 3., 4., 5. months, respectively). Results: Motor nerve conduction studies, performed in 1–4 months of clinical paresia initiation, revealed focal conduction blocks. Electrophysiological follow-up showed decreased distal CMAP amplitudes and denervation potentials supporting axonal degeneration in some; whereas increment in some other distal CMAP amplitudes, supporting early reversed conduction failures. This different patterns of conduction block resolution were documented both in different nerves of different patients and also in different nerves of the same patient. SNAPs were either decreased or preserved. Urine 2, 5-hexandion concentrations were between 1.45–4.52 mg. Discussion: n-Hexane gives cause to one of the most common toxic polyneuropathies seen in poorly ventilated factories. It is a sensory-motor polyneuropathy ending up with axonal degeneration. Nerve biopsy reveals paranodal axonal swelling and secondary myelin retraction in early stages. Myelin retraction imitates demyelination causing focal conduction block and failure before axonal degeneration emerges. This brings to mind the new category of nodo-paranodopathy described firstly for anti-ganglioside antibody mediated neuropathies, which can be proved by electrophysiological reevaluations. Significance: n-Hexane neuropathy may have a pathogenic mechanism of dysfunction/disruption at the node of Ranvier as another example of nodo-paranodopathy.